'A feeling you cannot resist': Shah Rukh Khan, affect, and the re-scripting of male stardom in Hindi cinema. Issue 3 (3rd July 2018) - Gopinath, Praseeda
ABSTRACT: While Shah Rukh Khan is considered to be the cinematic representation of Indian neoliberalism and global capitalism, the gendered dimensions of his stardom and personae are still thin on the ground. This paper theorizes the particular role of affect, emotion, and feeling in the gendered construction of Shah Rukh Khan as star text. Though affective masculinity has been central to male stardom in Hindi cinema, SRK shifted the focus from anger (Amitabh Bachchan's Angry Young Man) to vulnerability, sensitivity, and the ability to feel and endure pain. While these traits are still seen as constituent of the 'feminine, ' SRK deployed them with great effect to craft a new style of middle-class masculinity that shifted the accepted terms of masculinity without losing its heteronormative privilege. The paper explores three intertwined ideas: SRK's self-confessed 'hammy' tearful performances; his onscreen physical vulnerability, and sexual availability; and consequential to the above, how SRK signaled shifts in the cinematic representation of Indian middle-class masculinity. While the plots of SRK's films frequently reinforce heteronormative patriarchy, moments in his performance, along with the filmic representation of his body and face, contradict the linear inevitability of the triumph of patriarchal masculinity.